2006
DOI: 10.1002/anie.200602950
|View full text |Cite
|
Sign up to set email alerts
|

Chemo‐ and Regioselective Preparation and Reaction of a Kinetic Zinc Enolate Formed from a Thiol Ester and Bis(iodozincio)methane

Abstract: Reactive functionalized enolates that are otherwise difficult to obtain can be prepared in a simple procedure by the treatment of a thiol ester with bis(iodozincio)methane in the presence of a palladium catalyst (see scheme). The terminal zinc enolates thus formed are kinetically controlled and react with a variety of electrophiles, such as aldehydes, ketones, and acyl cyanides. FG=functional group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…We anticipated that 1a would react with nucleophile at C1 under extended Pummerer reaction conditions , to yield ketene dithioacetal 2 , which might be a very attractive intermediate for further transformation (Scheme ). Hydrolysis of ketene dithioacetal 2 could provide thiol ester 3 , which should react with nucleophile at C2 to give α-trifluoromethyl ketone 4 . Alternatively, reduction of 2 could afford dithiane 5 , which can participate in the conventional dithiane chemistry .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We anticipated that 1a would react with nucleophile at C1 under extended Pummerer reaction conditions , to yield ketene dithioacetal 2 , which might be a very attractive intermediate for further transformation (Scheme ). Hydrolysis of ketene dithioacetal 2 could provide thiol ester 3 , which should react with nucleophile at C2 to give α-trifluoromethyl ketone 4 . Alternatively, reduction of 2 could afford dithiane 5 , which can participate in the conventional dithiane chemistry .…”
mentioning
confidence: 99%
“…Treatment of ketene dithioacetal 9a with aqueous hydrochloric acid in acetonitrile followed by methylation yielded thiol ester 10 , which is a good electrophile in the reactions with various nucleophiles (Scheme ) . For instance, palladium-catalyzed cross-coupling reactions of thiol ester 10 with organozinc reagents afforded α-trifluoromethyl ketones 11a and 11b in good yields.…”
mentioning
confidence: 99%
“…Zinc enolates are an important class of reagents for organic synthesis, readily reacting with a range of electrophiles, and exhibiting lower basicity and greater functional group compatibility compared to their alkali metal counterparts. There are several common methods to access zinc enolates using stoichiometric zinc sources. , …”
mentioning
confidence: 99%
“…4 We had also shown that the palladium-catalyzed cross-coupling reactions of bis(iodozincio)methane with several thiol esters affords the zinc enolate selectively which corresponds to the terminal enolate of methyl ketone. 5,6 In this communication, we report on the chemo-, regio-and stereoselective preparation of silyl enol ethers based on the cross-coupling reaction of gem-dizincioalkane and various thiol esters (Scheme 1).…”
mentioning
confidence: 99%